A randomised controlled feasibility trial to evaluate Lawsonia inermis (henna)'s effect on palmar-plantar erythrodysesthesia induced by capecitabine or pegylated liposomal doxorubicin - Stavrinou, Michalis; Tsitsi, Theologia; Astras, George; Paikousis, Lefkios; Charalambous, Andreas (My University, 2021)
Purpose To test the effectiveness of henna in the management of palmar-plantar erythrodysesthesia (PPE) in patients receiving treatment with capecitabine or pegylated liposomal doxorubicin (PLD). Method This was a randomized controlled feasibility study in three specialized tertiary cancer centers with 56 patients with a PPE grade 1 or above and various cancer diagnoses. The intervention included the local application of henna to the affected areas. The control group followed the same process with a henna inert. Primary outcome was PPE grade and secondary outcomes were the EORTC QLQ-C30, PPE-related QoL (HFS-14), activities of daily living (ECOG) and pain. Patients in both groups were assessed at baseline and then weekly at four follow-ups. Results PPE grade in the intervention group (1–3.8%) was lower compared to the control group (4–13.38%) and also lower levels of pain were reported by the patients in the intervention group (2.46 ± 1.17) compared to the control (5.57 ± 2.01). ECOG status in the intervention group was improved compared to the control (p = 0.039). The intervention group, experienced higher Global Health Status (p ≤ 0.008), Physical function (p ≤ 0.001), Emotional Function (p = 0.029), Social function (p ≤ 0.001) and lower Fatigue (p ≤ 0.001) and Pain (p ≤ 0.001) compared to the Control group. A statistically significant interaction was found between Group and Time over the weekly measurements of HFS-14 scores (F = 5,009, p ≤ 0.002) indicating the significant effect of the intervention throughout the weekly assessments. Conclusion The trial provided preliminary evidence on henna's effectiveness for treating PPE during treatment with capecitabine or PLD, with lower PPE grades, better performance status and better HRQoL observed in the henna group.
Keywords: Hand-foot syndrome; Palmar-plantar erythrodysesthesia; Capecitabine; Henna; Quality of life; Symptom management; Pegylated liposomal doxorubicin